Taking Specialist Surgical Services to the Rural District Hospitals at One Forth Cost: A Sustainable ‘Return on Investment’ Public Health Initiative of Patan Hospital, Patan Academy of Health Sciences, Nepal - Shah, J.N. (Kathmandu University Medical Journal, 2017)
The inequitable distribution and centralization of resources and services in urban area persists around the world, more so in developing countries. The challenge to meet the health needs of rural population requires health policy makers, government and concerned organization to put extra efforts. Such efforts require innovative, feasible and sustainable strategies to address the social justice of people living in districts away from capital and urban cities. At Patan Academy of Health Sciences, the medial school curriculum is designed to address these issues. Together with health professionals from Patan Hospital, the main teaching hospital on which the academy evolved, have initiated strategies to bring specialist services, starting with surgical services to remote district hospitals to serve the need of rural population. This initiative is ‘desirable, doable and feasible’. Further more, this can be modified for replication and promotion by other academic institutions, central hospitals and government health system.